دور جودة معلومات التقارير المالية في تحقيق استقرار السوق المالية السعودية - منـــــاع, ريـــــمة (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
الملخص تهدف هذه الدراسة إلى قياس تطور مستوى الشفافية والإفصاح في التقارير المالية المنشورة من قبل الشركات المدرجة في السوق المالية خلال الفترة (2006-2014)م، وذلك لمعرفة مدى تطور جودة المعلومات المالية والاقتصادية في الشركات المدرجة في سوق الأسهم السعودي؛ ومدى انعكاسها على استقرار السوق المالية السعودية خلال نفس الفترة، لذا في هذا البحث تم تطبيق مؤشر الشفافية والإفصاح لمؤسسة S&P على 25 شركة مدرجة في السوق المالية السعودية، تم اختيارها بناءً على مجموعة من الشروط والإجراءات، ثم دراسة العلاقة بين مدى استقرار السوق المالية السعودية خلال الفترة(2006-2014)م وبين مستوى الشفافية والإفصاح في السوق المالية السعودية ككل. وفي الأخير تشير النتائج - إلى حد ما- إلى تحسن في جودة المعلومات المالية والاقتصادية التي تفصح عنها الشركات السعودية في التقارير المالية السنوية، كما أنه ليس علاقة تأثير معنوي بين المجموعات الفرعية لمؤشر الشفافية والإفصاح S&P وبين استقرار السوق المالية السعودية. الكلمات المفتاحية : الاستقرار المالي، جودة المعلومات، التقارير المالية السنوية، مؤشر الشفافية والإفصاح. ABSTRACT This study aims to measure the level of transparency and disclosure in financial reporting by companies introduced on the stock exchange during the period (2006-2014), and that in order to see the evolution of the quality of financial and economic information companies listed on the Saudi financial market and its impact on the stability of this market during the same period. To this end, we applied in our study; the transparency and disclosure index from S & P on 25 companies listed on the Saudi financial market are chosen with respect to certain criteria. Then we investigated the relationship between stability of the Saudi financial market during the period (2006-2014) and the level of transparency and disclosure of the Saudi financial market as a whole. Finally, the results reflect an improvement in the quality of financial and economic information disclosed by Saudi companies through the publication of financial reports, and no significant relationship between subsets of the transparency and disclosure index S & P and the stability of the Saudi financial market. Keywords: Financial Stability, The Quality Of Information, Annual Financial Reports, Transparency And Disclosure Index